2004
DOI: 10.1007/bf03345270
|View full text |Cite
|
Sign up to set email alerts
|

Eye muscle antibodies in Graves’ ophthalmopathy: Pathogenic or secondary epiphenomenon?

Abstract: The extra ocular (eye) muscles are one of the principal tissues involved in the autoimmune-mediated inflammation of Graves' ophthalmopathy (GO). Several eye muscle proteins are targeted by autoantibodies or sensitized T lymphocytes, or both, and include: G2s, which is now identified as the terminal 141 amino acids of the winged-helix transcription factor FOXP1, the flavoprotein (Fp) subunit of the mitochondrial enzyme succinate dehydrogenase, the so-called "64kDa protein", a non-tissue specific membrane protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…Patients treated with RTX were studied at 4,8,12,16,20,30,50, and 70-75 weeks, while those treated with IVGC were studied at 8, 20, 30, and 50 weeks after the first drug infusion (Fig. 1).…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients treated with RTX were studied at 4,8,12,16,20,30,50, and 70-75 weeks, while those treated with IVGC were studied at 8, 20, 30, and 50 weeks after the first drug infusion (Fig. 1).…”
Section: Patientsmentioning
confidence: 99%
“…It is known that both Th1 and Th2 cytokine patterns are involved and that the TSH receptor is expressed on orbital preadipogenic fibroblasts and may be a target for immunoglobulin G-stimulated hyperproduction of adipose tissue (5,6). There is no evidence of pathogenic autoantibodies, TRAb (7) and eye muscle-directed antibodies (8) occurring only at a second pathogenetic step or epiphenomena. Elevated serum TRAb levels have been correlated to the active phase of TAO (9), but this may not imply a role in the disease pathogenesis, since their titers have been shown not to vary in relation to the stabilization (10)(11)(12) and the duration of the clinical features (M Salvi et al unpublished observations).…”
Section: Introductionmentioning
confidence: 99%
“…More recent characterization of muscle antigens has focused on two proteins termed "G2s" and "Fp" (32). G2s is strongly expressed in thyroid and extraocular muscle, but is also present in skeletal muscle, myocardium, and other organs.…”
Section: Antibodies To Extraocular Musclementioning
confidence: 99%
“…On the basis of clinical information and neuro-imaging as well as serological data one can differentiate 2 subgroups of endocrine orbitopathy: ocular myopathy with pronounced swelling of the extra-ocular eye muscles, double vision and eye muscle paresis without significant inflammatory involvement of the orbital connective tissue on the one side, and orbitopathy with inflammatory changes of the periorbital fat body and proptosis with more or less involvement of the eye muscles [14]. The latter type is much more frequent compared to the first.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these authors found patients with involvement of both compartments which may represent a so-called mixed orbitopathy. Some antibodies are associated with the eye muscle type of endocrine orbitopathy (anti-G2s and anti-Fp antibodies), and other antibodies are more likely to be associated with the connective tissue type [14]. …”
Section: Discussionmentioning
confidence: 99%